2021
DOI: 10.3390/ma14113019
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Protein-Based Autophagy Biosensors

Abstract: Autophagy is an essential cellular process of self-degradation for dysfunctional or unnecessary cytosolic constituents and organelles. Dysregulation of autophagy is thus involved in various diseases such as neurodegenerative diseases. To investigate the complex process of autophagy, various biochemical, chemical assays, and imaging methods have been developed. Here we introduce various methods to study autophagy, in particular focusing on the review of designs, principles, and limitations of the fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…Employing correlative live-cell and super-resolution imaging (Balint et al, 2013; Verdeny-Vilanova et al, 2017) with sensors for autophagy (Kim and Seong, 2021), mTOR activity (Zhou et al, 2015), and luminal pH (Chin et al, 2021) could reveal more about these relationships. Previous studies in neurons showed that not all LAMP1-positive LELs contain degradative enzymes like cathepsin D. (Cheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Employing correlative live-cell and super-resolution imaging (Balint et al, 2013; Verdeny-Vilanova et al, 2017) with sensors for autophagy (Kim and Seong, 2021), mTOR activity (Zhou et al, 2015), and luminal pH (Chin et al, 2021) could reveal more about these relationships. Previous studies in neurons showed that not all LAMP1-positive LELs contain degradative enzymes like cathepsin D. (Cheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When autophagosomes fuse with lysosomes to become autolysosomes, the pH-sensitive red FP, but not the pH-stable blue FP, decreases its uorescent intensity. Therefore, real-time progression of autophagy can be monitored by measuring the red/blue (R/B) intensity ratios of RB-LC3 in live cells 20,22 .…”
Section: Autophagy Process For Mutant Htt Is Impairedmentioning
confidence: 99%
“…However, these conclusions were based on results from tandem EGFP-mCherry-LC3B experiments, which have technical limitations. For example, EGFP retains some mild fluorescence at a lysosomal pH, and a neutral pH buffer like the common fixative agent paraformaldehyde can restore GFP fluorescence that has been reduced due to lowered pH conditions [ 47 , 48 , 49 , 50 ]. Published guidelines exist for the standardization of methodology in studies of autophagy, with discussion of mitigation strategies [ 51 ].…”
Section: Role Of Vcp In the Cytosolmentioning
confidence: 99%